STUDI TEKNIK PENGELOLAAN KUALITAS AIR PADA PEMELIHARAAN INDUK UDANG VANNAMEI (Litopenaeus vannamei) DI PT. SURI TANI PEMUKA UNIT HATCHERY SINGARAJA, BALI - Maknun, Lu’lu’il; Sumsanto, Muhammad (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2023)
Vannamei shrimp (Litopenaeus vannamei) is one of the brackish water commodities that is in great demand by the public because it has economic value and is one of the leading products in the aquaculture sector in Indonesia. The purpose of this research was to study and find out about techniques for measuring air quality in rearing vannamei shrimp broodstock at PT. Suri Tani Pemuka, Singaraja Hatchery Unit, Bali. This research method is carried out by measuring and controlling air quality in containers that will be used for vanname shrimp broodstock cultivation activities. Air quality management activities in the maintenance of vaname shrimp (Litopenaeus vannamei) broodstock starts from the initial preparation, namely the sterilization of maintenance air media through the mixing process, sedimentation process, pressure filter, ozonation process, and finally the treatment process. The results of checking air quality carried out every day by measuring the parameters DO the result are 4,4-5,1 ppm, pH 7,6-7,8, Suhu 28,3-28,5oC, Salinitas 30-31 ppt, Alkalinitas 111-113 ppm, Nitrit (NO2) 0,11-0,4 ppm, Amonium (NH4) 0,55-0,87 ppm, obtained the results of air quality measurements that were still at optimal levels that supported the life of the vanname shrimp broods that were reared .